Central field perimetry of discriminated targets: I. Results for normal individuals using high-contrast targets - (:unkn) unknown (NATURE PUBLISHING GROUP, 2009)
Purpose A new perimetry method is described to evaluate central vision under multiple hue, illumination, and contrast conditions; results are described for normal individuals using high-contrast targets. Methods For 70 normal eyes of individuals with varying age, the ETDRS chart acuity was determined as well as discriminated target perimetry using high-contrast targets presented for 250 ms at locations up to 10 degrees eccentricity. Retesting was performed to evaluate for learning and repeatability for the thresholded acuity at each eccentricity. Results The ETDRS acuity averaged 1.15 +/- 0.37 arc min minimum angle of resolution (MAR) with best correction (20/23 equivalence). At fixation, the thresholded acuity for high-contrast targets paralleled the ETDRS acuity and averaged 1.75 +/- 0.85 arc min MAR (20/35 equivalence), and declined with increasing eccentricity in a linear fashion to 5.81 +/- 3.97 arc min (20/116 equivalent) at 10 degrees eccentricity. Linear regression showed Vmar = 1.74 vertical bar 0.330 * eccentricity in degrees (R-2 = 0.966, P < 0.0001). Testing time required similar to 8-10 min per eye. Repeated testing showed only minimal learning experience at the most peripheral locations. The test-retest 95% confidence limits of difference measured 1.12 arc mins MAR at fixation (64% of the mean) and remained approximately the same proportion to the mean thresholded acuity outwards to 10 degrees eccentricity. Conclusion The methodology seems rapid and reliable for measuring discriminatory visual function of optotype targets throughout the central 20 degrees diameter visual field. Eye (2009) 23, 2082-2089; doi:10.1038/eye.2009.177; published online 17 July 2009
Keywords: discriminated target; perimetry; visual acuity; visual field; resolution; Landolt C; VISUAL-ACUITY; DIABETIC-RETINOPATHY; MACULAR DEGENERATION; EYE-MOVEMENTS; LETTER CHARTS; OLDER-ADULTS; AGE; SENSITIVITY; RESOLUTION; VISION